Ridolfia segetum Moris (false fennel) response to different rates of application of Metsulfuron Methyl - B, Hajjaj; A, El Oualkadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
Abstract: High infestations of Ridofia segetum can cause wheat crops yield reduction. The aim of this study is to investigate the effect of Metsulfuron Methyl on R. segetum infestation in a soft wheat crop. The experimental design was Randomized Complete Block Design (RCBD) with three replications. Each block contained 4 elementary plots, 3 plots of which were treated with three rates of application of Metsulfuron Methyl and one untreated control plot. Trial were conducted in Ouazzane region of Morocco in January 2018. Treatments were carried out with a knapsack sprayer with the nozzle delivering a 3 bar jet. A quadrant of 1m x 1m was used to calculate percentage of R. segetum density reduction and biomass reduction. R. segetum dry biomass were determined using an oven at 75 ° C for 48 hours. Then, weighed with a precision balance. Results showed that treatments with Metsulfuron Metsulfuron Methyl at 6 g/ha and 9 g/ha gave the best control of R. segetum infestations recording respectively 92.5% and 94.6% of R. segetum density reduction and 92.7% and 94.6% of R. segetum dry biomass reduction. Metsulfuron Methyl at 3 g/ha recorded the lowest efficacies 61.9 and 48.8% respectively on R. segetum density reduction, and R. segetum dry biomass reduction.